Geothermal energy: Present use, Resources and Technology - Duque, Maria Rosa (2013)
Abstract. In this work we use a data-base compiled by the IGA to examine the increase of geothermal energy use in recent years. We speak about electricity produced by different plant types and direct uses of geothermal fluids. We can conclude that the use of geothermal energy has tended to increase in recent years. According to the IGA, there are 233 geothermal plants planned to be in operation in the coming years. The direct use of geothermal fluids is increasing especially the use of geothermal heat pumps. The last part of the work is dedicated to geothermal resources and future research related to this subject. We discuss different problems related to each type of resource and present the benefits that their exploration can bring to humanity, especially those related to air pollution.